Effect of Salicylidene Salicylhydrazide on Testes of Albino Mice: A Histomorphological Study (European journal of volunteering and community-based projects, 2021)
There is recently an increasing reports of reduction in sperm counts along with other reproductive disorders that is ascribe to the use of drugs and environmental chemicals. In this regard conducting toxicological studies on male reproductive is of paramount importance. This study evaluates salicylidene salicylhydrazide (SCS) for any possible toxicological effects on male reproductive system. Male BALB/c mice were daily administered withSCSat 5, 25, and 50 mg/kg for 7 and 14 days. The body and testes weights were measuredand the testes were subjected to histological tissue processing techniques. The extent of testicular toxicity was evaluated by using modified Johnsen scoring system for assessing the level of spermatogenesis, and morphometric analysis by measuring the diameter of the seminiferous tubules, thickness of germinal epithelium, and area of interstitial cells of Leydig. The body and testes weights showed that the various doses of SCS have no substantial effects after 7 and 14 days. The tested doses of SCS did not produce any distinguishable change in the normal histological features of seminiferous tubules and interstitium after 7 days. However, after 14 days, the 50 mg/kg dose of SCS was associated with vacuolization and loosening of germinal epithelium. These mild-to-moderate histopathological aberrations was confirmed from morphometric analysis in this dose group in which a decrease in the seminiferous tubules diameter and reduction in the thickness of germinal epithelium along with an increase in the interstitial area were observed. These findings concluded that SCS is considered to be relatively safe.